Redox nanoparticle treatment protects against neurological deficit in focused ultrasound-induced intracerebral hemorrhage. (July 2012) - Chonpathompikunlert, Pennapa; Fan, Ching-Hsiang; Ozaki, Yuki; Yoshitomi, Toru; Yeh, Chih-Kuang; Nagasaki, Yukio
Background: Intracerebral hemorrhage is reported to induce the generation of reactive oxygen species and oxidative DNA damage in the brain.Aims: We aimed to examine whether our designed redox polymer nanoparticle could reduce intracerebral hemorrhage induced by 1-MHz focused ultrasound sonication coupled with microbubble treatment.Materials & methods: Contrast-enhanced ultrasound imaging, frozen section, brain edema, neurologic deficit, the number of morphologically normal neurons, DNA oxidization and superoxide anion generation were used to investigate the neuroprotective effect of redox polymer nanoparticles.Results: We confirmed that the 1-MHz focused ultrasound coupled with microbubble produced intracerebral hemorrhage and showed that the redox polymer nanoparticle ameliorates intracerebral hemorrhage-induced brain edema, neurological deficit and oxidative damage.Conclusion: These results suggest that redox polymer nanoparticle is a potential therapeutic agent for intracerebral hemorrhage induced by focused ultrasound. Original submitted 23 June 2011; Revised submitted 24 October 2011; Published online 6 March 2012